2013
DOI: 10.9767/bcrec.9.1.5258.16-22
|View full text |Cite
|
Sign up to set email alerts
|

Enolisation Kinetics of m-Nitro Acetophenone

Abstract: Abstractm-Nitroacetophenone has been chosen for the study of kinetics of enolisation. Enolisation reactions have been carried out using four different amino acids viz. β-alanin, DL-alanin, L-alanin and Glycine. The rate of the reaction has been studied by iodination. Kinetics of the reaction has been monitored under several conditions by variation of ketone concentration, dielectric constant of the medium, temperature, effect of catalysts, etc. for the enolisation process. The rate of enolisation has been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…m-Methylacetophenone is a colorless liquid used as a reagent in organic synthesis. Amino acids too on the other hand have been tested for their catalytic activity on a number of substances (Malhotra and Jaspal, 2014;Rodina and Godson, 2006;Zhong et al, 2012;Vassilev et al, 2013). However no substantial work has been carried out in order to study the catalytic potential of these biomolecules in the enolisation of m-Methylacetophenone which remains the main motive of this research work.…”
Section: Introductionmentioning
confidence: 98%
“…m-Methylacetophenone is a colorless liquid used as a reagent in organic synthesis. Amino acids too on the other hand have been tested for their catalytic activity on a number of substances (Malhotra and Jaspal, 2014;Rodina and Godson, 2006;Zhong et al, 2012;Vassilev et al, 2013). However no substantial work has been carried out in order to study the catalytic potential of these biomolecules in the enolisation of m-Methylacetophenone which remains the main motive of this research work.…”
Section: Introductionmentioning
confidence: 98%
“…The keto form is thermodynamically more stable than the enol form, but some factors, such as dielectric constant and hydrogen bond-forming ability of solvent, temperature, concentration, catalyst, and substituent groups, shift the equilibrium in favor of the enol form. For instance, more polar keto form in a polar solvent is the predominant tautomeric form due to the solvation effect [8, [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, water was used as a catalyst to increase the rate of enolization reactions. It is found that free energy of activation of keto-enol tautomerization process decreases in the presence of one or two water molecules [16,17,21,28,31]. It also seems that water molecules control the pathway of aldol reaction by decreasing or increasing the formation rate of enol intermediate, in other words, the enol content of the carbonyl compound.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, there have been an extensive number of kinetic studies on the keto‐enol equilibrium mostly on acetophenone or acetyl heterocycle derivatives in water [11–18] with only a few studies on molecules similar to BnFTP [19,20] and an even more limited number in organic solvents [21] . Every kinetic study carried out on the enolization of carbonyls was assessed by either deuteration, racemization, or halogenation, [13] the latter one being the most used [11–18,22−24] . Here we use the racemization approach, conducted with a polarimeter set‐up that continuously samples the racemizing mixture to the polarimeter cell, using a recycle loop connected to the reactor in order to measure directly the enantiomeric excess of the compound during the racemization reaction.…”
Section: Introductionmentioning
confidence: 99%